Influence of diets supplemented with tryptophan on self-balancing, feed intake and productive performance in white cachama (Piaractus brachypomus) - Carolina Quintero-Pardo, Ana Maria [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (Univ Caldas, 2016)
This study evaluated the ability of juvenile white Pirapitinga to select food with different tryptophan content in order to self-balance the amino acid intake using information originated from the food source. Therefore, how Tryptophan (Trp) intake affected self-balance of food and productive performance is assessed. The experiment consisted in providing diets supplemented with Trp and a control diet to juveniles with initial weight from 46.99 to 47.59 g as follows: Rc (0.32% Trp - control ration), R2 - 0.64% Trp, R4 - 1.28% Trp and R6 - 1.92% Trp. The number of the diet corresponds to the number Trp was multiplied by in the control diet. Two hand-made feeders were used at the bottom of the aquarium in which 2% of the fish live weight was placed in each diet per day for 14 days. The results showed that the white Pirapitinga was able to self-balance the daily consumption of Trp, benefiting food consumption, weight gain and standard length, as well as food conversion. In conclusion, juvenile Pirapitinga can regulate the tryptophan consumption at a 0.80% level in the diet, equivalent to 20.69 mg/day.
Keywords: feed intake; Fish; Pirapitinga; self-selection